PENGEMBANGAN JARINGAN TRANSMISI 150 KV BALI BERDASARKAN RENCANA UMUM KETENAGALISTRIKAN DAERAH (RUKD) PROVINSI BALI TAHUN 2022 – 2030 - I G.N. Evan Aditya Pramana; W.G. Ariastina; I.W. Sukerayasa (Program Studi Teknik Elektro UNUD, 2023)
The need for electrical energy increases every year. That is linear with the economic growth that happens in the area. Bali is an area where the demand for electrical energy has increased significantly throughout the year. The increase in electrical energy demands will cause the power peak load to increase as well. It's necessary to develop a 150 kV transmission system to anticipate peak load from reaching the breakdown point of the transmission system. Based on this study, the transmission line from Kapal Substation to Pemecutan Klod Substation experienced 80.1% of the maximum load capacity of the line in 2029. It means that the load flow has exceeded the ideal loading of the transmission line, which is 80% of its maximum capacity. Uprating the conductor from TACSR 240 mm2 to ACCC Lisbon 310 mm2 and adding a new circuit line, will help the transmission line sustainable until 2046 before reaching 100% of its maximum capacity.